IL-15 Mediates Mitochondrial Activity through a PPARδ-Dependent-PPARα-Independent Mechanism in Skeletal Muscle Cells - Thornton, Shantaé M.; Krolopp, James E.; Abbott, Marcia J. (PPAR Research, 2016)
Molecular mediators of metabolic processes, to increase energy expenditure, have become a focus for therapies of obesity. The discovery of cytokines secreted from the skeletal muscle (SKM), termed “myokines,” has garnered attention due to their positive effects on metabolic processes. Interleukin-15 (IL-15) is a myokine that has numerous positive metabolic effects and is linked to the PPAR family of mitochondrial regulators. Here, we aimed to determine the importance of PPARα and/or PPARδ as targets of IL-15 signaling. C2C12 SKM cells were differentiated for 6 days and treated every other day with IL-15 (100 ng/mL), a PPARα inhibitor (GW-6471), a PPARδ inhibitor (GSK-3787), or both IL-15 and the inhibitors. IL-15 increased mitochondrial activity and induced PPARα, PPARδ, PGC1α, PGC1β, UCP2, and Nrf1 expression. There was no effect of inhibiting PPARα, in combination with IL-15, on the aforementioned mRNA levels except for PGC1β and Nrf1. However, with PPARδ inhibition, IL-15 failed to induce the expression levels of PGC1α, PGC1β, UCP2, and Nrf1. Further, inhibition of PPARδ abolished IL-15 induced increases in citrate synthase activity, ATP production, and overall mitochondrial activity. IL-15 had no effects on mitochondrial biogenesis. Our data indicates that PPARδ activity is required for the beneficial metabolic effects of IL-15 signaling in SKM.